If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 = 5x + -16 Reorder the terms: 5 + 2x = 5x + -16 Reorder the terms: 5 + 2x = -16 + 5x Solving 5 + 2x = -16 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + 2x + -5x = -16 + 5x + -5x Combine like terms: 2x + -5x = -3x 5 + -3x = -16 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + -3x = -16 + 0 5 + -3x = -16 Add '-5' to each side of the equation. 5 + -5 + -3x = -16 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = -16 + -5 -3x = -16 + -5 Combine like terms: -16 + -5 = -21 -3x = -21 Divide each side by '-3'. x = 7 Simplifying x = 7
| 9p^2r-73pr-70r=0 | | -.75x=-6 | | r+19=27 | | 4a+8b+11a-10b= | | 5x-1-4x=1x+7 | | 3(7x+6y)=6x | | 3+6x=x-7 | | 2(x+3)+4x=6x+6 | | 6y=8+-9+6y | | 23=11+n | | 4x-6(2x+8)= | | n+2.4=-6.5 | | 0.5(2x-2)=5x+4 | | 4x+7y=71 | | x^2=8100 | | 4x-3x-5=x | | 0.04n=7.2 | | 5(-3x-3)=120 | | 79-2x=16x+15 | | ln*(x-22)=39 | | -2(4y+6)= | | 2x+1=4+4x-3 | | 3.15=15y | | 3=-3n-(-5n+1) | | 2+8x=4(2x+2)-6 | | -4k=9k | | -5h=-32/3 | | 16x^2-88x+121=0 | | -1x+4=7x-3 | | 8x-73=4x-9 | | 6a-5(8-3a)= | | 4k-8k=-6 |